Strategi Bimbingan Mudabbir untuk Memotivasi Santri Baru dalam Menghafal Al Quran di Ponpes Tahfidzul Qur’an Al Ishlahuddy Kediri Lombok Barat - Heriyadi Heriyadi; Hamzanwadi; Azhar (HARAPAN: Jurnal Ilmu Kesehatan dan Psikologi, 2025)
Santri as human resources and are the main factor supporting prosperity in facing the era of society 5.0. The condition of santri who are living in the boarding school is not as beautiful as imagined, especially new santri who have just arrived in the boarding school environment. Judging from their young age, then separated from their parents and living with other people and not in their residential environment, all of these are very difficult situations and conditions for new santri to go through. The formulation of the problem in this study is How is the mudabbir guidance strategy to motivate new santri in memorizing the Qur'an at the Al-Ishlahuddiny Kediri West Lombok Tahfizul Qur'an Islamic Boarding School? And What is the form of motivation for new santri in memorizing the Qur'an at the Al-Ishlahuddiny Kediri West Lombok Tahfizul Qur'an Islamic Boarding School? The researcher used a descriptive qualitative research method that aims to identify a picture or variable, or several variables, without drawing comparisons or relationships between these variables and other factors with observation, interview, and documentation data collection techniques. The research results that researchers obtained in the field were; First, related to the strategy of mudabbir guidance to motivate new students in memorizing the Qur'an at the Al-Ishlahuddiny Tahfizul Qur'an Islamic Boarding School, Kediri, West Lombok, are 1) submitting memorization, 2) giving appreciation, and 3) providing control. Then the form of motivation for new students in memorizing the Qur'an at the Al-Ishlahuddiny Tahfizul Qur'an Islamic Boarding School, Kediri, West Lombok, is 1) enthusiasm, 2) discipline, and 3) memorization according to target.